Kewenangan Mediator dalam Penyelesaian Perkara Perceraian: Studi Kasus Pengadilan Agama Majene - Alimuddin, Hardiyanti; Amaliah, Rezki; Syam, Sitti Mutmainnah (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2023)
Mediation is a process of resolving disputes between two or more parties through negotiations or consensus. Mediation proceedings also occur in divorce disputes. The main problem in this study is the role and function of mediators in divorce disputes at the Majene Religious Court and the supporting factors and inhibiting factors of mediators in the Majene Religious Court. The purpose of the study was to determine the role and function of mediators in divorce disputes at the Majene Religious Court and how the supporting and inhibiting factors of mediators in the Majene Religious Court. The type of research used is field research with a normative theological approach to syar'i. Researchers use two data sources, namely primary data and secondary data. In the data collection method, researchers make observations, interviews, and documentation. The procedure for conducting research is the preparatory stage, operational stage, and completion stage. Data analysis with data reduction steps, data presentation, and data verification. The results showed that the existence of mediators in the Religious Justice system, especially in the Majene Religious court, was by Perma rules and carried out their duties as mediators as neutral parties in reconciling the parties. In addition, the function and role of mediators in resolving the problems of people who want to divorce are very necessary because reconciliation efforts are a burden required by law to judges in every examination, trial, and decision of divorce cases. The supporting factor of the mediator in resolving divorce disputes is having experience training the mediator certificate so that it can mediate the parties well. The inhibiting factor of the mediator in mediating is the desire of the parties to remain divorced and if the parties make tantramen (violence, emotion, anger) to the mediator. This study implies that married couples must be aware of the marriage bond they have pledged uphold the vow/promise and strive for maturity. The a need to conduct training for judges on their main duties and as mediators on an ongoing basis by paying attention to talent as mediators. Thus, it is recommended to the community, including shari'ah scholars who have competence in the field of family law, to attend mediator training to obtain a mediation certificate to play a role in efforts to reconcile divorce litigants in the Religious Court.